External load of soccer players in the moments before and after a goal - Jose Antonio Asián clemente; Iván Asín Izquierdo; Diego Mueriarte; José Vicente Beltrán Garrido; Carlos Galiano de la Rocha (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Research has explored factors linked to scoring goals in soccer, but little is known about teams' external load when a goal occurs.